2012
DOI: 10.7193/dm.065.31.43
|View full text |Cite
|
Sign up to set email alerts
|

 Les suremballages : des emballages superflus pour les consommateurs ?

Abstract: Les suremballages, des emballages superflus pour les consommateurs ? Les pratiques domestiques des consommateurs à l'égard des suremballagesElisa MONNOT Fanny RENIOU Résumé Actuellement, les politiques gouvernementales prônent une réduction à la source des suremballages (cartons entourant les produits sans qu'il n'y ait de regroupement d'unités primaires). Celle-ci aura des répercussions certaines sur les stratégies des industriels en termes de conception des packagings. Dans ce contexte, il paraît nécessaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
3
0
3
Order By: Relevance
“…As part of an exploratory approach, certain researchers sought to circumscribe the 'doctrine' of sustainable development (Flipo, 2004;Lauriol, 2004). Others focused on consumers in an effort to understand their representations and the meaning of responsible consumption on the one hand (Elgaaïed, 2013;Gonzales et al, 2009;Monnot and Reniou, 2012;Özçağlar-Toulouse, 2009), or to better understand their decision to purchase so-called sustainable products on the other hand (Böcker et al, 1991;Daniel, 2013;François-Lecompte and Valette-Florence, 2006;Giannelloni, 1998;Rémy, 2004). Recent studies have also shown that resistance to products associated with sustainable development is not only linked to pricing but also to the moral stance associated with the discourse on ecology (Monnot and Reniou, 2013) or to the difficulties in identifying with these products (Gurviez and Sirieix, 2013;Pernin and Petitprêtre, 2012).…”
Section: Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of an exploratory approach, certain researchers sought to circumscribe the 'doctrine' of sustainable development (Flipo, 2004;Lauriol, 2004). Others focused on consumers in an effort to understand their representations and the meaning of responsible consumption on the one hand (Elgaaïed, 2013;Gonzales et al, 2009;Monnot and Reniou, 2012;Özçağlar-Toulouse, 2009), or to better understand their decision to purchase so-called sustainable products on the other hand (Böcker et al, 1991;Daniel, 2013;François-Lecompte and Valette-Florence, 2006;Giannelloni, 1998;Rémy, 2004). Recent studies have also shown that resistance to products associated with sustainable development is not only linked to pricing but also to the moral stance associated with the discourse on ecology (Monnot and Reniou, 2013) or to the difficulties in identifying with these products (Gurviez and Sirieix, 2013;Pernin and Petitprêtre, 2012).…”
Section: Sustainable Developmentmentioning
confidence: 99%
“…• Meanings and experiences of responsible consumption (Elgaaïed, 2013;Gonzales et al, 2009;Monnot et Reniou, 2012;Özçaglar-Toulouse, 2009) • Diverse forms of sustainable development: frugality, voluntary simplicity, citizen-consumer, etc. (McDonagh, Dobscha et Prothero, 2011;Varey, 2010) • Motivations, tensions and resistance to purchasing (Böcker, Hausruckinger et Herker, 1991;Daniel, 2013;Flipo, 2004;François-Lecompte et Valette-Florence, 2006;Giannelloni, 1998;Gurviez et Sirieix, 2013;Lauriol, 2004;Monnot et Reniou, 2013;Pernin et Petitprêtre, 2012;Rémy, 2004) • Dominant paradigm and social, political and cultural transformations (Kilbourne et Mittelstaedt, 2011) • Opposition between materialism and sustainable development (Mick et al, 2011) • Consumer-producer relations (Béji-Bécheur, Fosse- Gomez et Özçaglar-Toulouse, 2005;Bocquet, 2013;Dampérat et Dussart, 2007;de Ferran et al, 2013;Dufeu et Ferrandi, 2013;Robert-Demontrond et Özçaglar-Toulouse, 2011) • Marketing tools that favour sustainable development (Binninger et Robert, 2013;Gabriel, 2003) Health…”
Section: Povertymentioning
confidence: 99%
“…Dans une visée exploratoire, des travaux ont appréhendé la « doctrine » du développement durable (Flipo, 2004 ;Lauriol, 2004). D'autres recherches se sont focalisées sur les consommateurs pour comprendre leurs représentations et les significations liées à la consommation responsable, d'une part (Elgaaïed, 2013 ;Gonzales et al, 2009 ;Monnot et Reniou, 2012 ;, ou pour mieux appréhender leurs décisions d'achat de produits dits durables, d'autre part (Böcker, Hausruckinger et Herker, 1991 ;Daniel, 2013 ;François-Lecompte et Valette-Florence, 2006 ;Giannelloni, 1998 ;Rémy, 2004). De récents travaux montrent aussi que la résistance aux produits associés au développement durable n'est pas seulement liée à une logique de prix, mais aussi à la moralisation impliquée par les discours sur l'écologie (Monnot et Reniou, 2013) ou encore aux difficultés d'identification aux produits (Gurviez et Sirieix, 2013 ;Pernin et Petitprêtre, 2012).…”
Section: Développement Durableunclassified
“…Concerning incoming flows, because amassing large volumes of waste is a physical constraint, reducing the volume of waste coming into the home could be encouraged. In this context, both the authorities and manufacturers could encourage people to buy products with less (Monnot and Reniou, 2012), compactable or rechargeable packaging (for example in the form of labelling on products, similar to labels such as 'Made in France'). Concerning outgoing flows, more hygienic collection systems could be designed to respond to certain consumers' need for cleanliness (for example by providing containers with flaps that can be opened with the feet rather than with the hands).…”
Section: Managerial Implicationsmentioning
confidence: 99%